Pathogenetic Role of the Mitral Valve at Hypertrophic Cardiomyopathy - Zakharova, V. P.; Rudenko, O. V.; Trembovetska, O. M.; Zakhartseva, L. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Abstract.The work is devoted to the results of the study of the role of the mitral valve (MV) in the pathogenesis of hypertrophic cardiomyopathy (HCM). Purpose. To determine the role of MV in the pathogenesis of HCM. Morphological examination was performed on the operating material: 36 MV fragments, 41 specimens of the interventricular septum resected during Ferrazzi surgery, 4 autopsy cases of aortic valve stenosis (AVS). Morphological data were compared with the results of Echocardiography: 41 patients with HCM (29 men and 12 women, mean age – 39.8 ± 15.3 years), 53 patients with AVS (comparison group), 54 healthy volunteers (24 men and 30 women, mean age – 33.2 ± 8.5 years). Echocardiograms of maximal longitudinal displacement of the basal segments of the left ventricle were analyzed. The results were processed using the Statistica 6.0 application package. At HCM changes of MV in the form of atypical chords are attached, which are attached to the smooth part of the ante-rior flap, destruction of the endothelial layer on the ventricular surface of this flap, increase of the sizes of the flap and chord, expansion of the spongy and fibrosis of the compact layer. In the basal part of the interventricular septum a fibrous stain is formed on the endocardium. In the area of the myocardium adjacent to the mitral fibrosis stain, maximal hypertrophy of cardiomyocytes and interstitial fibrosis spreading from the fibrous stain are observed. Asymmetric contraction of the basal segments of the LV was reported in patients with HCM with vector-echocardiogram by reducing the longitudinal displacement of the septal, inferior and anterior segments and increasing this index for the posterior and lateral walls. This indicates the asymmetric nature of the reduction of the LV myocardium, resulting in the MV fibrous ring during systole shifting unevenly. In patients with AVS, circular myocardial hypertrophy due to stenosis does not affect MV position during systole. According to the study, morpho-functional evidence was obtained of the essential role of MV in the development of HCM, but the question remains open and needs further study.